2020
DOI: 10.1016/j.cognition.2019.104107
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual switching between languages and listeners: Insights from immersive virtual reality

Abstract: Perhaps the main advantage of being bilingual is the capacity to communicate with interlocutors that have different language backgrounds. In the life of a bilingual, switching interlocutors hence sometimes involves switching languages. We know that the capacity to switch from one language to another is supported by control mechanisms, such as task-set reconfiguration. This study investigates whether similar neurophysiological mechanisms support bilingual switching between different listeners, within and across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 102 publications
(177 reference statements)
7
30
1
Order By: Relevance
“…The present results also showed reversed language dominance: faster responses when naming in L2 than in L1 in mixedlanguage blocks. The reversed language dominance has been reported in studies examining unbalanced bilinguals (e.g., Costa and Santesteban, 2004;Christoffels et al, 2007;Gollan and Ferreira, 2009;Verhoef et al, 2009;Peeters et al, 2014;Kleinman and Gollan, 2016;Peeters and Dijkstra, 2018;Wu et al, 2018;Liu et al, 2019;Peeters, 2020). The present study showed a global slowdown of the L1 across semantic conditions in switch trials.…”
Section: Language Switching: Mixing Costs Reversed Language Dominancsupporting
confidence: 81%
“…The present results also showed reversed language dominance: faster responses when naming in L2 than in L1 in mixedlanguage blocks. The reversed language dominance has been reported in studies examining unbalanced bilinguals (e.g., Costa and Santesteban, 2004;Christoffels et al, 2007;Gollan and Ferreira, 2009;Verhoef et al, 2009;Peeters et al, 2014;Kleinman and Gollan, 2016;Peeters and Dijkstra, 2018;Wu et al, 2018;Liu et al, 2019;Peeters, 2020). The present study showed a global slowdown of the L1 across semantic conditions in switch trials.…”
Section: Language Switching: Mixing Costs Reversed Language Dominancsupporting
confidence: 81%
“…In the late time window of the picture-locked ERPs, we also observed a switch-related negativity, which is in line with the findings of Kang et al (2020), Peeters (2020, and Peeters and Dijkstra (2018). According to Kang and colleagues, this pattern represents an N400-like component such that word meaning retrieval is more difficult during switch trials.…”
Section: Picture-locked Erpssupporting
confidence: 91%
“…For example, there is no short peak in the picture-locked waveforms that resembles an N2 component, and the difference between switch and repetition trials seems to occur broadly across the scalp rather than being constrained to anterior sites. Not observing a typical switch-related N2 over anterior sites is not entirely surprising, since this component does not seem robust across studies (e.g., Christoffels et al, 2007;Martin et al, 2013;Peeters, 2020;Peeters & Dijkstra, 2018;Timmer et al, 2019;Verhoef et al, 2009). Instead, it looks like the pattern in the early time window of the picturelocked data may reflect the beginning of the pattern that we see in the late time window.…”
Section: Picture-locked Erpsmentioning
confidence: 77%
See 2 more Smart Citations